Calcitriol, the Bioactive Metabolite of Vitamin D, Increases Ventricular K+ Currents in Isolated Mouse Cardiomyocytes - Tamayo, María; Martin-Nunes, Laura; Val-Blasco, Almudena; Piedras, Maria J.; Larriba, María J.; Gómez-Hurtado, Nieves; Fernández-Velasco, María; Delgado, Carmen (Frontiers in Physiology, 2018)
Calcitriol, the bioactive metabolite of vitamin D, interacts with the ubiquitously expressed nuclear vitamin D receptor (VDR) to induce genomic effects, but it can also elicit rapid responses via membrane-associated VDR through mechanisms that are poorly understood. The down-regulation of K+ currents is the main origin of electrophysiological remodeling in pathological hypertrophy and heart failure, which can contribute to action potential prolongation and subsequently increase the risk of triggered arrhythmias. We hypothesized that calcitriol modulates K+ currents in mouse ventricular myocytes. Adult mouse ventricular myocytes were isolated and treated with 10 nM calcitriol or vehicle for 15–30 min. In some experiments, cardiomyocytes were pretreated with the Akt inhibitor triciribine. In adult mouse ventricles, outward K+ currents involved in cardiac repolarization are comprised of 3 components: the fast transient outward current (Itof), the ultrarapid delayed rectifier K+ current (Ikur), and the non-inactivating steady-state outward current (Iss). K+ currents were investigated using the whole-cell or the perforated patch-clamp technique and were normalized to cell capacitance to obtain current densities. Calcitriol treatment of cardiomyocytes induced an increase in the density of Itof and Ikur, which was abolished in myocytes isolated from VDR-knockout mice. In addition, calcitriol activated Akt in cardiomyocytes and pretreatment with triciribine prevented the calcitriol-induced increase of outward K+ currents. In conclusion, we demonstrate that calcitriol via VDR and Akt increases both Itof and Ikur densities in mouse ventricular cardiomyocytes. Our findings may provide new mechanistic clues for the cardioprotective role of this hormone in the heart